Analysis of the Quality of Assessment Questions of Standardized Regional Assessment (ASPD) of Junior High School Reading Literacy : A Review Based on Barret's Taxonomy Cognitive Levels - Himawan, Riswanda; Rahayu, Triwati; Alfian, Muhammad Afnani; Hermawan, Muhammad Alfian (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the quality of practice questions of Asessemen Standarisasi Penilaian Daerah (ASPD) Indonesian language junior high school in Bantul Regency, Yogyakarta in terms of the cognitive level of Barret's taxonomy. This research employed qualitative research.Â The data source of this research was the question document of Package A, which was adopted from MGMP Indonesian language junior high school in Bantul Regency. The theory used to analyze these questions was the theory of Barret's Taxonomy. The results of the analysis stated that there were 14 questions with literal comprehension taxonomy, 6 items included in reorganization comprehension, 6 implied comprehension, 1 question included in the evaluation comprehension category and 1 question included in evaluation comprehension. This research is expected to contribute to providing references to teachers, especially Indonesian language teachers in Bantul to develop questions, practice reading comprehension questions for students to improve the DIY ASPD program which will later lead to PISA with the hope of increasing the PISA scores and rankings of Indonesian students.